2006
DOI: 10.1111/j.1526-4610.2006.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Myofascial Trigger Points and Their Relationship to Headache Clinical Parameters in Chronic Tension‐Type Headache

Abstract: Active TrPs in upper trapezius, sternocleidomastoid, and temporalis muscles were associated with CTTH. CTTH subjects with active TrPs usually reported a greater headache intensity and longer headache duration than those with latent TrPs. CTTH subjects with active TrPs tended to have a greater FHP than CTTH subjects with latent TrPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
132
4
21

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(165 citation statements)
references
References 16 publications
8
132
4
21
Order By: Relevance
“…examination tests (Lous and Olesen 1982;Langemark and Olesen 1987;Bovim 1992;Hatch et al 1992;Garrett et al 1993;Jensen et al 1993;Kidd and Nelson 1993;Watson and Trott 1993;Jensen 1996;Lipchik et al 1996;Sand et al 1997;Zwart 1997;Ashina et al 1999;Jull et al 1999Jull et al , 2007Neufeld et al 2000;Dumas et al 2001;Mørk et al 2003;Giacomini et al 2004;Fernández-de-las-Peñas et al 2006;Fernández-de-Las-Peñas et al 2006a, 2006b, 2007Sandrini et al 2006;Zito et al 2006;Amiri et al 2007;Glaros et al 2007Glaros et al , 2007Ogince et al 2007;Hall et al 2008Hall et al , 2010Hall et al , 2010Bevilaqua-Grossi et al 2009;Peddireddy et al 2009;Uthaikhup et al 2009;Sohn et al 2010Sohn et al , 2013Stuginski-Barbosa et al 2010;Melo et al 2012;Watson and Drummond 2012;Marchand et al 2014;Tali et al 2014). …”
Section: A C C E P T E D Accepted Manuscriptunclassified
“…examination tests (Lous and Olesen 1982;Langemark and Olesen 1987;Bovim 1992;Hatch et al 1992;Garrett et al 1993;Jensen et al 1993;Kidd and Nelson 1993;Watson and Trott 1993;Jensen 1996;Lipchik et al 1996;Sand et al 1997;Zwart 1997;Ashina et al 1999;Jull et al 1999Jull et al , 2007Neufeld et al 2000;Dumas et al 2001;Mørk et al 2003;Giacomini et al 2004;Fernández-de-las-Peñas et al 2006;Fernández-de-Las-Peñas et al 2006a, 2006b, 2007Sandrini et al 2006;Zito et al 2006;Amiri et al 2007;Glaros et al 2007Glaros et al , 2007Ogince et al 2007;Hall et al 2008Hall et al , 2010Hall et al , 2010Bevilaqua-Grossi et al 2009;Peddireddy et al 2009;Uthaikhup et al 2009;Sohn et al 2010Sohn et al , 2013Stuginski-Barbosa et al 2010;Melo et al 2012;Watson and Drummond 2012;Marchand et al 2014;Tali et al 2014). …”
Section: A C C E P T E D Accepted Manuscriptunclassified
“…For instance, in a patient with frequent episodic tension type headache where the peripheral input is mainly dominant, a manual therapy approach including inactivation of active trigger points in the upper trapezius, 47 sternocleidomastoid ( Fig. 1), 48 temporalis, 49 suboccipital (Fig. 2), 50 extra-ocular superior oblique 51 or extraocular lateral rectus 52 muscles (Fig.…”
Section: Manual Therapy Strategies For Headachesmentioning
confidence: 99%
“…In addition, they demonstrated that active as compared with latent MTrPs in the head and neck muscles examined were associated with greater headache intensity and frequency. 13,14 Both Fernandez-de-las-Penas et al and Danish researchers observed that active MTrPs were significantly more frequent in patients with CTTH than in control persons. [13][14][15] A group of Korean researchers also found a significantly greater number of active MTrPs in patients with CTTH as compared to those with episodic tension-type headache, with no active MTrPs in the control group.…”
Section: Introductionmentioning
confidence: 96%
“…• Minor criteria: 13,14 They demonstrated in blinded controlled studies of patients with CTTH recruited from a hospital neurology department that palpation of active MTrPs in the upper trapezius, suboccipital, sternocleidomastoid and temporalis muscles produced referred pain which reproduced the patient's usual headache. In addition, they demonstrated that active as compared with latent MTrPs in the head and neck muscles examined were associated with greater headache intensity and frequency.…”
Section: Introductionmentioning
confidence: 99%